EVALUASI KESESUAIAN JALUR EVAKUASI BENCANA TSUNAMI DI KECAMATAN KUTA RAJA KOTA BANDA ACEH MENGGUNAKAN SISTEM INFORMASI GEOGRAFI - Firjannah, Putri; Furqan, M. Hafizul (Jurnal Spasial, 2025)
Earthquakes that cause tsunamis have occurred in Indonesia, one of which was in Aceh Province in 2004. Thisstudy aims to evaluate the suitability of tsunami evacuation direction signs in Kuta Raja District based on predetermined parameters. This research is a laboratory research, data collection techniques in the form of literature studies and field surveys with data analysis using Overlay techniques and value scores on GIS Software. Based on the results of the study, it is known that topographically the Kuta Raja District area is on average at an altitude of 0-3 masl, with the farthest distance from the coastline is about 2.5 Km. Land use in Kuta Raja District is dominated by settlements with an area coverage of about 55% of the total area. The results of the analysis showed that there were as many as 14 directional signs indicating the Tsunami disaster evacuation route throughout the Kuta Raja District area indicating the direction of the appropriate path for community evacuation, however, there were several evacuation route signs that were constrained by road widths that only ranged from 4-6 m and several road bodies that were damaged.